Peanut Genotypes with Reduced Content of Immunogenic Proteins by Breeding, Biotechnology, and Management: Prospects and Challenges - Tariq Alam; Sachin Rustgi (Plants)
Peanut allergies affect millions of people worldwide, often causing life-threatening reactions and necessitating strict avoidance. Recent advancements in oral immunotherapy, such as Palforzia™, and IgE-mediated treatments (e.g., Xolair), have improved care options; however, their high costs limit accessibility and widespread utility. To address these challenges, researchers are employing conventional breeding and advanced molecular tools, such as CRISPR editing, to develop peanut lines with reduced levels of major allergenic proteins (Ara h1, Ara h2, Ara h3, and Ara h6). These reduced-immunogenicity genotypes retain their agronomic viability, flavor, and nutritional quality to some extent, offering the potential for cost-effective oral immunotherapy and safe food options for use in public spaces by non-allergic individuals. Rigorous evaluation, including immunological assays and human feeding trials, is essential to confirm their effectiveness in reducing allergic reactions. Adoption will depend on the establishment of clear regulatory guidelines, stakeholder education, and transparent communication of the benefits and risks. With sustained research, public trust, and supportive policies, reduced-immunogenicity peanuts could substantially lower the global burden of peanut allergies. This communication examined the impact of peanut allergies worldwide and explored strategies to develop peanut genotypes with reduced allergen content, including conventional breeding and advanced genetic engineering. It also addressed the challenges associated with these approaches, such as policy and regulatory hurdles, and outlined key requirements for their successful adoption by farmers and consumers.